Job satisfaction, burnout, and depression in nurses working in level 2 and level 3 intensive care units - Gonderen, Kamil; Yucens, Bengu (Annals of Medical Research, 2021)
Aim: This study aimed to determine the burnout, job satisfaction and depression levels of second and third level intensive care unit (ICU) nurses and whether there was a difference between the groups in terms of these characteristics. The relationship between burnout, job satisfaction, and depression levels in ICU nurses was also investigated.Material and Methods: The study included 42 level 2 and 43 level 3 ICU nurses. A sociodemographic data form, the Minnesota Job Satisfaction Scale (MJS), Maslach Burnout Inventory (MBI), and Beck Depression Inventory (BDI) were applied to the participants. Statistical analysis was performed using the t-test, Pearson correlation, and multiple linear regression analysis.Results: There was no significant difference between the groups in terms of MJS, MBI subscales, and BDI scores. There was a negative correlation between the duration of work in ICU and job satisfaction however, no significant correlation between the duration of work in ICU and burnout and depression levels. There was a negative correlation between job satisfaction and emotional exhaustion, depersonalization, depression levels also a positive correlation between personal accomplishments. Emotional exhaustion and personal accomplishment predicted job satisfaction, whereas depersonalization and depression did not.Conclusion: To protect mental health and increase job satisfaction of ICU nurses, precautions should be taken to reduce burnout and depression.
Keywords: Burnout; depression; intensive care unit; job satisfaction; nurse